2008
DOI: 10.1371/journal.pgen.1000069
|View full text |Cite
|
Sign up to set email alerts
|

An Inducible and Reversible Mouse Genetic Rescue System

Abstract: Inducible and reversible regulation of gene expression is a powerful approach for uncovering gene function. We have established a general method to efficiently produce reversible and inducible gene knockout and rescue in mice. In this system, which we named iKO, the target gene can be turned on and off at will by treating the mice with doxycycline. This method combines two genetically modified mouse lines: a) a KO line with a tetracycline-dependent transactivator replacing the endogenous target gene, and b) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 40 publications
(49 reference statements)
0
57
0
Order By: Relevance
“…Previous work showed that TRE-driven genes targeted (via a retrovirus) to the mouse TIGRE locus, situated on Chromosome 9 between the AB124611 (HIDE1) and Carml loci, could be expressed in most tissues in the presence of tTA (Zeng et al, 2008). However, targeting of TRE driven transgenic cassette to the Rosa26 locus resulted in silencing or mosaicism of the transgene expression (Tasic et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that TRE-driven genes targeted (via a retrovirus) to the mouse TIGRE locus, situated on Chromosome 9 between the AB124611 (HIDE1) and Carml loci, could be expressed in most tissues in the presence of tTA (Zeng et al, 2008). However, targeting of TRE driven transgenic cassette to the Rosa26 locus resulted in silencing or mosaicism of the transgene expression (Tasic et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…To complement existing Cre driver lines, we focused on the intersection of Cre with another recombinase or with a transcriptional activator. In addition, we built and validated a new docking site in a permissive genomic locus, the TIGRE locus (Zeng et al, 2008), which supports repeated targeting. By introducing a tTA-based transcriptional amplification approach to the TIGRE locus, all reporter lines doubly regulated by Cre and tTA drove robust expression of sensors and effectors at levels substantially higher than those in comparable Rosa-CAG based reporters.…”
Section: Introductionmentioning
confidence: 99%
“…The BFP/mCherry FUCCI reporter (pEN435) was assembled by serial modification of the base vector vector pFNF (Addgene #22687) using Gibson assembly with the following templates: hGeminin and mCherry-Cdt1 were PCR amplified from pRetroX-S2G2M and pRetroX-G1-Red (Clonetech); tagBFP cDNA from pHR-Tet3G-2A-BFP (Kind gift from Stanley Qi); CAGGS promoter and puroR are of the same source as pEN113; homology arms to the Tigre locus (Zeng et al, 2008) were PCR amplified from E14Tg2A genomic DNA (1kb each).…”
Section: Methods Detailsmentioning
confidence: 99%
“…This idea has partially been based on the observation that statins – potent anti-inflammatory drugs developed to lower cholesterol by blocking endogenous cholesterol synthesis – resulted in regression of atherosclerotic plaques in individuals with coronary heart disease 66 . Likewise, inducible reconstitution of ApoE in mice expressing a hydromorphic ApoE allele or that lack ApoE demonstrated diminished atherosclerotic plaques and foam cell content 67, 68 . On the other hand, aggravation of atherosclerosis is associated with increased accumulation of macrophages, which possibly lost their ability to leave the plaque.…”
Section: The Removal Of Plaque Macrophagesmentioning
confidence: 99%